Comparison between TightRail rotating dilator sheath and GlideLight laser sheath for transvenous lead extraction. Issue 5 (27th March 2021) - Qin, Dingxin; Chokshi, Moulin; Sabeh, Mohamad Khaled; Maan, Abhishek; Bapat, Aneesh; Bode, Weeranun D.; Hanley, Alan; Hucker, William J.; Ng, Chee Yuan; Funamoto, Masaki; Barrett, Conor D.; Mela, Theofanie
Abstract: Background: There are limited data on the comparative analyses of TightRail rotating dilator sheath (Philips) and laser sheath for lead extraction. Objective: To evaluate the effectiveness and safety of the TightRail sheath as a primary or secondary tool for transvenous lead extraction (TLE). Methods: Retrospective cohort analysis of 202 consecutive patients who underwent TLE using either TightRail sheath and/or GlideLight laser sheath (Philips) in our hospital. The study population was divided into three groups: Group A underwent TLE with laser sheath only ( N  = 157), Group B with TightRail sheath only ( N  = 22), and Group C with both sheaths ( N  = 23). Results: During this period, 375 leads in 202 patients were extracted, including 297 leads extracted by laser sheath alone, 45 leads by TightRail sheath alone, and 33 by both TightRail sheath and laser sheaths. The most common indications included device infection (44.6%) and lead‐related complications (44.1%). The median age of leads was 8.9 years. TightRail sheath (Group B) achieved similar efficacy as a primary extraction tool compared with laser sheath (Group A), with complete procedure success rate of 93.3% (vs. 96.6%, P  = .263) and clinical success rate of 100.0% (vs. 98.1%, P  = .513). Among 32 leads in which Tightrail was used after laser had failed (Group C), the complete procedure success rate was 75.8%. No significant difference in procedural adverse events was observed. Conclusion: Our single‐center experience confirms that the TightRail system is an effective first‐line and second‐line method for TLE. Further investigation is required to guide the selection of mechanical and laser sheaths in lead extraction cases.